2021
DOI: 10.1177/17423953211039783
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue self-management led by occupational therapists and/or physiotherapists for chronic conditions: A systematic review and meta-analysis

Abstract: Objective The aim of this study was to investigate the effectiveness of occupational therapist-/physiotherapist-guided fatigue self-management for individuals with chronic conditions. Methods Eight databases, including MEDLINE and EMBASE, were searched until September 2019 to identify relevant studies. Randomised controlled trials and quasi-experimental studies of self-management interventions specifically developed or delivered by occupational therapists/physiotherapists to improve fatigue symptoms of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The duration and dose of self-managing education regarding fatigue has been discussed recently as an important part in receiving larger effects, especially because it aims for behavioral changes. 19 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…The duration and dose of self-managing education regarding fatigue has been discussed recently as an important part in receiving larger effects, especially because it aims for behavioral changes. 19 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the results of the present study revealed more profound fatigue among individuals with lower levels of physical activity. Fatigue by itself may justify the lack of exercise or physical activity (28), immobility, and a sedentary lifestyle, which can, in turn, lead to persistent fatigue. Physical exercise is believed to decrease fatigue and promote HRQoL, regardless of the exercise type.…”
Section: Discussionmentioning
confidence: 99%
“…Further, self-management programs combining aerobic training, energy conservation management, and relapse prevention have been shown to improve social participation and functional endurance in patients with neuromuscular diseases and chronic fatigue [75,76]. Moreover, cognitive behavioural therapy (CBT) can ameliorate experienced chronic fatigue in patients with neuromuscular diseases [77,78].…”
Section: Optimizing Clinical Care For Selenon-rm Patientsmentioning
confidence: 99%